The role of internal auditing to support in maintaining corporate governance preference An Applied Study on Private Banks in Iraq - Dlshad mohammedsaleh yousif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The technological and scientific progress that accompanied this era led to an increase in the number and size of economic organizations, and thus an increase in the responsibilities assigned to these organizations to implement their goals. Moreover, the complexity of administrative problems resulting from the practice of various activities makes internal audit an urgent need imposed by the nature of modern scientific management to preserve the financial resources provided to these organizations. The success that the organization aims for depends on the fertile environment and the dialectical relationship between the individual’s success and the organization’s success. When the organization is part of the indeterminacy, success is the mutual benefit of both the organization and the differentiation depending on the hegemony of the inferior system and the justice between the individuals. The concept of organizational nanny succeeds in developing the relationship between the founders and investing in markets and other investors because of its clear importance to the economic situation of public and private participating organizations and society in general. Financial crises led to the press, justice, and the American financial community to search for the vital role of administrative boards, audit committees, senior management, and external and internal auditors in organizational organization processes. All this participation in one way or another in the organizational possession by emphasizing the efficiency of operations, following and obeying the rules and regulations that demonstrateconfidence in financial reports, caring for the financial position of organizations and maintaining an acceptable level of risk if they their duties properly. In light of the aforementioned, in addition to supporting the nanny in the organizations, strengthening the guidance, management and control systems will achieve or implement the goals of the organization automatically without any interference or effects to maintain the treatment control between the organizations all the relevant individuals. Therefore, the researcher will focus on the role and function of the internal audit and its effects on the organizational governance process in order to support it in response to the interests of the various parties in society, the public and private sectors.